Determination of the coefficient of secondary compression on reconstituted sand bed/Smėlinio pagrindo antrinės deformacijos koeficiento nustatymas - Parasonis, Josifas; Gabrielaitis, Linas (Journal of Civil Engineering and Management, 2001)
Experimental results on reconstituted sand bed are described to define the coefficient of secondary compression in sand. Two samples of Ticino sand were reconstituted at two different relative densities (DR ≅ 40 and 85%). The observed settlements have been compared to those inferred from a conventional computation Schmertmann method. This method provides an excellent provision of the primary settlement occurring in freshly deposited Ticino sand. The coefficient of secondary compression Cαε was determined from the data of experimental results. Using the correlations regression analysis, dependences of Cαε calculation are suggested. And equations (3) for low-density sand and (5) for high-density sand have been obtained. Equation (7) determines a common case. Equations (3), (5) and (7) were approbated by comparison of computed and observed [10] secondary settlements.Article in Lithuanian.First Published Online: 30 Jul 2012